Development and efficacy of NXY-059 for the treatment of acute ischemic stroke. (May 2008) - Papadakis, Michalis; Nagel, Simon; Buchan, Alastair M
NXY-059 is a neuroprotective compound that prevents ischemic damage by trapping free radicals. Preclinical animal stroke models demonstrated that the agent is able to reduce histological damage and improve behavioral outcome. Phase II studies showed that NXY-059 administration does not cause any serious adverse events and it is well tolerated by both healthy volunteers and stroke patients. The first Phase III trial indicated that NXY-059 treatment results in a small, but significant improvement of the primary neurological outcome, as measured by the modified Rankin scale. However, NXY-059 did not improve coprimary outcomes assessed by the NIH Stroke Scale (NIHSS) and the Barthel index. For patients receiving thrombolysis together with NXY-059, there was an associated reduction of symptomatic intracerebral hemorrhage. Although NXY-059 showed positive results in this Phase III study, a larger scale Phase III study revealed that the efficacy of NXY-059 is not better than placebo in treating acute stroke patients. Hence, NXY-059 failed to materialize as an effective acute stroke treatment. This article summarizes the path of the drug from bench to bedside and points out what possibly went wrong. How such an outcome can be prevented in future trials for neuroprotective agents will also be discussed.